2013
DOI: 10.1104/pp.113.227637
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis PECTIN METHYLESTERASEs Contribute to Immunity against Pseudomonas syringae

Abstract: Pectins, major components of dicot cell walls, are synthesized in a heavily methylesterified form in the Golgi and are partially deesterified by pectin methylesterases (PMEs) upon export to the cell wall. PME activity is important for the virulence of the necrotrophic fungal pathogen Botrytis cinerea. Here, the roles of Arabidopsis PMEs in pattern-triggered immunity and immune responses to the necrotrophic fungus Alternaria brassicicola and the bacterial hemibiotroph Pseudomonas syringae pv maculicola ES4326 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 89 publications
1
123
0
Order By: Relevance
“…The regulation of the DM of HG has been implicated in many aspects of plant development (Wolf et al, 2009a), including cell adhesion (Tieman and Handa, 1994;Wen et al, 1999;Mollet et al, 2000;Bouton et al, 2002;Mouille et al, 2007;Durand et al, 2009), adventitious rooting (Guénin et al, 2011), primordia emergence at the shoot apical meristem (Peaucelle et al, 2008(Peaucelle et al, , 2011, fruit ripening (Brummell and Harpster, 2001;Phan et al, 2007), and plant defense (Bethke et al, 2014). Although data have shown an important role for Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the DM of HG has been implicated in many aspects of plant development (Wolf et al, 2009a), including cell adhesion (Tieman and Handa, 1994;Wen et al, 1999;Mollet et al, 2000;Bouton et al, 2002;Mouille et al, 2007;Durand et al, 2009), adventitious rooting (Guénin et al, 2011), primordia emergence at the shoot apical meristem (Peaucelle et al, 2008(Peaucelle et al, , 2011, fruit ripening (Brummell and Harpster, 2001;Phan et al, 2007), and plant defense (Bethke et al, 2014). Although data have shown an important role for Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Bromphenol blue was added, and the sample was heated at 80°C for 10 min and then separated by SDS-PAGE using 10% acrylamide gel and transferred to nitrocellulose membrane for 1500 mA h. Western blots were blocked with 5% (w/v) nonfat dry milk in Tris-buffered saline (TBS) supplemented with 3% Tween 20; incubated with peroxidase-antiperoxidase-soluble complex (Sigma) or the indicated antiserum and the appropriate secondary serum at 1:2500 dilution for 2 h each; and detected with chemiluminescence. PME Activity-The Ruthenium Red agar diffusion assay was adapted from Bethke et al (15). 0.1% pectin Ն85% esterified (Sigma P9561), 1% agarose, 12.5 mM citric acid, 50 mM Na 2 HPO 4 , pH 7.0, was microwaved, and 13 ml was poured per 10-cm Petri dish.…”
Section: Methodsmentioning
confidence: 99%
“…Pectins are also the target of numerous pathogens that digest the wall as they approach the plant cell, thereby generating de-esterified pectin fragments or oligogalacturonides (OGs) (13,14). Numerous studies demonstrate that OGs can activate a stress response by the plant, indicating that OGs signal pathogen presence (15).…”
mentioning
confidence: 99%
“…In a recent study on Arabidopsis PMEs, revealed that PMEs affect patterns of methylesterification in a way that impart pattern-triggered immunity to Pseudomonas syringae pv maculicola ES4326 (Pma ES4326) [79]. Oils from coconut germ, sunflower seed, palm kernel, rape seed are industrially extracted with organic solvents.…”
Section: Other Applicationsmentioning
confidence: 99%
“…3.1.1.11), a methyl ester group hydrolytic enzyme is produced by plants, pathogenic fungi, and bacteria also constantly being used in the wine, juice, and other food industries [1]. In Arabidopsis PMEs, it was revealed that PMEs have unique patterns of methylesterification that provide immunity to Pseudomonas syringae pv maculicola ES4326 (Pma ES4326) [2]. Pectin methylesterase catalyzes reactions according to the double-displacement mechanisms, de-esterification through transferring the C 6 carboxyl groups in the pectin-PME complexes to water molecules altering the degree and pattern of methyl esterification and transacylation through transferring the C 6 carboxyl groups to the hydroxyl groups of another pectin molecules and resulting in the formation of high molecular weight pectins with new non-methoxy ester linkages [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%